PEMANFAATAN MEDIA SOSIAL YOUTUBE SEBAGAI PERSONAL BRANDING CONTENT CREATOR - Fitriany, Rysha Mutiara; Suryasuciramdhan, Arfian; Sucitasari, Lisna Febriyanti; Fatimah, Kheisya Maura; Munir, Thasya Azhari (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
This study aims to examine the communication strategy in building Bianca Kartika’s personal branding on the YouTube platform by applying Peter Montoya’s eight laws of personal branding theory. The background of this research lies in the importance of personal branding as a tool to differentiate oneself and build strong relationships with audiences in a highly competitive digital era. The research method used is descriptive qualitative, with data collected through observation of video content, audience interactions, and analysis of comments and engagement on Bianca Kartika’s YouTube channel. The results indicate that Bianca Kartika consistently applies Montoya’s eight laws, ranging from specialization in Korean culture content, showcasing an authentic and friendly personality, to maintaining high visibility through regular content uploads and active engagement with her followers. This strategy not only strengthens her image as an inspiring and trustworthy content creator but also fosters a positive emotional connection with her audience. The study concludes that Montoya’s personal branding theory is highly relevant and effective when applied in the context of social media and digital influencers, particularly for building and sustaining a strong personal brand on YouTube. Keywords: Bianca Kartika, Communication Digital, Social Media, Personal Branding,